Poisoning by Marijuana (Revista da Faculdade de Direito, Universidade de São Paulo, 1988)
The Autor analyses diagnostic criteria for "cannabis" intoxication, resumes data on motivation for use and clinical symptoms, illustrating his exposition with a forensic case.